Clinical and microbiological features of patients admitted to the intensive care unit with nursing and healthcare-associated pneumonia. (April 2015) - Lee, Myoung Kyu; Kim, Sang-Ha; Yong, Suk Joong; Shin, Kye Chul; Park, Hyeon Cheol; Choi, Jiwon; Choi, Yeun Seoung; Seong, Jae Ho; Jung, Ye-Ryung; Lee, Won-Yeon
Objective: To evaluate clinical and microbiological features in patients with nursing and healthcare-associated pneumonia (NHCAP), admitted to the intensive care unit (ICU). Methods: Demographic, clinical and microbiological data were retrospectively reviewed from patients with NHCAP admitted to a respiratory ICU. Patients were categorized into one of four NHCAP groups: (A) residence in a long-term nursing-home setting or healthcare home; (B) hospital discharge in the preceding 90 days; (C) elderly or physically disabled patients who stay at home but require healthcare; (D) continuously receiving outpatient endovascular therapy including chronic dialysis, anticancer drugs, and immunosuppressants. Pneumonia severity index (PSI), CURB-65, duration of ICU stay and 30-day mortality were evaluated. Results: Out of 428 patients reviewed (male, 67.1%; mean age, 71.2 ± 11.9 years), 30-day mortality was 25.5%, and duration of ICU stay was 13.8 ± 13.3 days. Mortality rate was not significantly different between the four NHCAP groups; duration of ICU stay was significantly longer in groups C and D. PSI score, serum HCO3 – level, duration of ICU stay, extended spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae and multidrug resistant (MDR) Acinetobacter baumannii were significantly associated with 30-day mortality. Conclusion: ESBL-producing K. pneumoniae, MDR A. baumannii and PSI score should be considered in ICU patients with NHCAP.